Experiential knowledge of risk and support factors for physician performance in Canada: a qualitative study - Kain, Nicole Allison (BMJ Open, 2019)
OBJECTIVE: To identify, understand and explain potential risk and protective factors that may influence individual and physician group performance, by accessing the experiential knowledge of physician-assessors at three medical regulatory authorities (MRAs) in Canada. DESIGN: Qualitative analysis of physician-assessors’ interview transcripts. Telephone or in-person interviews were audio-recorded on consent, and transcribed verbatim. Interview questions related to four topics: Definition/discussion of what makes a ‘high-quality physician;’ factors for individual physician performance; factors for group physician performance; and recommendations on how to support high-quality medical practice. A grounded-theory approach was used to analyse the data. SETTING: Three provinces (Alberta, Manitoba, Ontario) in Canada. PARTICIPANTS: Twenty-three (11 female, 12 male) physician-assessors from three MRAs in Canada (the College of Physicians & Surgeons of Alberta, the College of Physicians and Surgeons of Manitoba and the College of Physicians and Surgeons of Ontario). RESULTS: Participants outlined various protective factors for individual physician performance, including: being engaged in continuous quality improvement; having a support network of colleagues; working in a defined scope of practice; maintaining engagement in medicine; receiving regular feedback; and maintaining work-life balance. Individual risk factors included being money-oriented; having a high-volume practice; and practising in isolation. Group protective factors incorporated having regular communication among the group; effective collaboration; a shared philosophy of care; a diversity of physician perspectives; and appropriate practice management procedures. Group risk factors included: a lack of or ineffective communication/collaboration among the group; a group that doesn’t empower change; or having one disruptive or ‘risky’ physician in the group. CONCLUSIONS: This is the first qualitative inquiry to explore the experiential knowledge of physician-assessors related to physician performance. By understanding the risk and support factors for both individual physicians and groups, MRAs will be better-equipped to tailor physician assessments and limited resources to support competence and enhance physician performance.